2010
DOI: 10.1007/s00467-010-1448-7
|View full text |Cite
|
Sign up to set email alerts
|

Primary focal segmental glomerulosclerosis in Egyptian children: a 10-year single-centre experience

Abstract: Primary focal segmental glomerulosclerosis (FSGS) in children accounts for 7-20% of all cases of idiopathic nephrotic syndrome (NS). To evaluate the clinical course of children with primary FSGS, the records of 72 patients with biopsy-proven FSGS admitted between 1995 and 2008 were retrospectively analysed. Forty-eight patients were male (66.7%). The mean age at presentation was 76.5 +/- 54 (range 12-192) months. The mean duration of follow-up was 76.3 +/- 42 (range 9-156) months. Seventeen patients (23.6%) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
5
10
0
1
Order By: Relevance
“…We also observed that 61 % of 113 patients with FSGS were-steroid-resistant. These data are in agreement with those of other studies that show a preponderance of steroid resistance among children with FSGS [33,34,37]. In the International Study of Kidney Disease in Children study, two thirds of 37 patients with FSGS did not respond to steroids [36].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We also observed that 61 % of 113 patients with FSGS were-steroid-resistant. These data are in agreement with those of other studies that show a preponderance of steroid resistance among children with FSGS [33,34,37]. In the International Study of Kidney Disease in Children study, two thirds of 37 patients with FSGS did not respond to steroids [36].…”
Section: Discussionsupporting
confidence: 94%
“…It should be pointed out, however, that other studies also reported that resistance to steroids is a much better predictor of CKD in children with INS than the pathological diagnosis of FSGS [34,36,41]. In line with these studies, our findings have clearly shown that initial response to steroids is a good predictor of long-term renal survival in children with INS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have previously reported the unfavorable prognosis of our patients with SRNS-FSGS. 9 Although the number of patients reported in this study was small with short duration of follow up, it was observed that in patients bearing NPHS2 mutations the disease started earlier, all of them had FSGS and none of them developed ESRD. However, the other clinical characteristics were comparable in patients with NPHS2 mutations and those without.…”
Section: Discussionmentioning
confidence: 95%
“…The FSGS-CT findings support significant differences in demographic features between histologic subtypes. Tip and collapsing variants were more common in teenagers and adults than children (5,6,12,(14)(15)(16)(17)(18)(19). Only 29% of tip patients were children aged 2-12 years at onset of FSGS, whereas 43% were over 18 years.…”
Section: Discussionmentioning
confidence: 99%